Avaliação da eficácia terapêutica do xarope composto por justicia pectoralis, plectranthus amboinicus e mentha arvensis na asma - Linhares, José Henrique (2012)
The pharmacological research, numerous chemical and agronomic plants received a strong boost in 2008 when the Federal Government approved the National Program for Medicinal Plants and Herbal Medicines, published in a ministerial decree signed by the Ministry of Health Plans in popular use (with bronchodilator, anti-inflammatory, laxative, parasiticide, anti-hypertensive, anti-ulcerogenic, ...) have received increased attention. The objective of this study was to evaluate the therapeutic efficacy of syrup Justicia pectoralis, Plectranthus amboinicus and Mentha arvensis (Chamba) in patients with asthma, to evaluate the effectiveness of the syrup in the quality of life and pulmonary function tests in patients with asthma, bronchodilator therapy and expand the therapeutic options to SUS users with access to herbal safety, efficacy and quality. In this context, the study proposes the use of syrup composed of Justicia pectoralis, Plectranthus amboinicus and Mentha arvensis, plants of the National Medicinal Plant Interest rates (RENISUS) through prospective clinical trial of the double-blind, placebo-controlled randomized parallel. The conducting a clinical trial using this herbal in patients with asthma resulted in an attempt to achieve other therapeutic option to be used in combination with the medication to minimize the symptoms and improve the quality of life of patients. The therapeutic use of Chamba syrup, used in 35 patients with mild asthma, as a complementary therapy, although not presenting changes in parameters of pulmonary function tests, showed an improvement in quality of life through the results of the questionnaire Quality of Life Standardized Asthma Activities - AQLQ (S), without causing toxicity or adverse effects. It can be concluded that to analyze the quality of life AQLQ (S) of the patients and placebo groups Chamba during 28 days of the trial it was found that in both groups, the scores of the symptoms observed in the field D7 (P <0,01), D14 (P <0,001) and D28 (P <0,001) were significantly higher than that observed before treatment (D0).